Elastic, charge transfer, and related transport cross sections for proton impact of atomic hydrogen for astrophysical and laboratory plasma modeling. (5th April 2016) - Schultz, D R; Ovchinnikov, S Yu; Stancil, P C; Zaman, T
Abstract: Updating and extending previous work (Krstić and Schultz 1999 J. Phys. B: At. Mol. Opt. Phys. 32 3458 and other references) comprehensive calculations were performed for elastic scattering and charge transfer in proton—atomic hydrogen collisions. The results, obtained for 1301 collision energies in the center-of-mass energy range of 10 −4 –10 4 eV, are provided for integral and differential cross sections relevant to transport modeling in astrophysical and other plasma environments, and are made available through a website. Use of the data is demonstrated through a Monte Carlo transport simulation of solar wind proton propagation through atomic hydrogen gas representing a simple model of the solar wind interaction with heliospheric neutrals.